Step-by-step analytical synthesis of the mathematical model of automotive unmanned aircraft - A. A. Lobaty; A. Y. Bumai; S. S. Prohorovith (Системный анализ и прикладная информатика, 2021)
The problem of the stage-by-stage synthesis of the mathematical model of the autopilot of an unmanned aerial vehicle (UAV) is considered. At the first stage, an analytical synthesis of the control acceleration applied to the center of mass of the UAV is performed to form a specified trajectory of its flight. On the basis of the results received at the first stage, at the subsequent stages, the problem of synthesizing a mathematical model of the UAV autopilot is solved with the specified requirements for ensuring the stability and dynamic accuracy of UAV control. Under actual assumptions about the corresponding nature of changes in the trajectory parameters and variables that characterize the motion of the UAV in space, the use of a linear mathematical model of the evolution of the state vector of the UAV and its control system is substantiated. When synthesizing a mathematical model of the UAV autopilot, the method of modal control of the system was used for a specified mathematical model of the object. For a specified model of motion and aerodynamic characteristics of the UAV, the law of deviation of the control steering surface is analytically received, which depends on the parameters of the translational and rotational movement of the UAV. Computer simulation of the analytically received results of control synthesis for the specified characteristics of UAVs and specific using conditions was carried out, which clearly showed the efficiency and prospects of using this approach for the synthesis of control systems for UAVs of various purposes and design.